Missions in the Oecumenical Movement (International review of mission, 1952)
Books Reviewed in this article: Ecumenical Foundations: A history of the International Missionary Council and its Nineteenth-Century Background. By William Richey Hogg. New York: Harpers. USD5.00. Obtainable London: Hamish Hamilton. 40s. 1952. Apprenticeship at Kuruman: Being the journals and letters of Robert and Mary Moffat, 1820–1828. Edited by I. Schapera. Illustrated. Map. Central African Archives, Oppenheimer Series, No. 5. London: Chatto and Windus. 30s. 1951. The Year Book of Education 1951. Edited by J. A. Lauwerys and N. Hans. London: Evans Brothers, in association with the University of London Institute of Education. 63s. 1951. Conflict and Conciliation of Cultures. By Ralph Tyler Flewelling. Stockton, California: College of the Pacific Press. USD3.00. 1951. African Systems of Kinship and Marriage. Edited by A. R. Radcliffe-Brown and Daryll Forde. London: Oxford University Press (for the International African Institute). 35s. 1951. The Position of the Chief in the Modern Political System of Ashanti. By K. A. Busia. London: Oxford University Press (for the International African Institute). 18s. 1951. The Christian in the World Struggle. By M. M. Thomas and J. D. McCaughey. Geneva: World's Student Christian Federation. On sale London: S.C.M. 5s. N.Y.: United Student Christian Council. USD1.00. 1951. Florence Allshorn and the Story of St Julian's. By J. H. Oldham. London: S.C.M. Press. 12s. 6d. N.Y.: Harpers. USD2.75. 1951. A Church Born to Suffer. By John Rose. London: Cargate Press. 5s. 1951. Into Red Starlight. By Douglas Thompson. London: Edinburgh House Press. 3s. 6d. 1951. Christ Came to Bitter Market. By W. F. Rowlands. London: Livingstone Press. 2s. 6d. 1951. Memoirs of the Reverend Dr Shirley Waldemar Baker, D.M., LL.D., Missionary and Prime Minister. By Lilian and Beatrice Shirley Baker. Illustrated. London: Mayflower Publishing Co. Ltd. 15s. 6d. 1951. Seven Tribes of British Central Africa. Edited by Elizabeth Colson and Max Gluckman. Illustrated. Maps. London: Oxford University Press. 37s. 6d. 1951. Gramophone Records of African Music. African Music Research directed by Hugh Tracey. Johannesburg: Gallo (Africa) Ltd. July, 1951.